Penerapan Media Papan Perkalian Pecahan (Paperca) Berbasis Model Problem Based Learning untuk Meningkatkan Minat Belajar Matematika Siswa Kelas VI SD Negeri Tugurejo 02 - Yulianti, Dyah Rahmah; Purwati, Panca Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was motivated by problems experienced by teachers, namely that students had difficulty in multiplying natural numbers with fractions, which made students' learning outcomes low and their interest in learning multiplication quite low. The aim of this research is to increase students' interest in learning, especially in the material of multiplying natural numbers with fractions. The subjects in this research were 32 class VI students at SD Negeri Tugurejo 02. Data collection techniques for researchers include interviews, questionnaires and documentation. The data analysis technique in this research uses qualitative descriptive data analysis techniques. The results of this research show that the application of the Fraction Multiplication Board (Paperca) media based on the Problem Based Learning (PBL) model can increase interest in learning mathematics, the material for multiplying natural numbers with fractions.